VITAMIN C AND PHYSICOCHEMICAL PARAMETERS IN THE MATURATION OF Berberis lobbiana “UNTUSHA” - Rosales Laguna, Dyana Daysi (2015)
Berberis lobbiana is an Andean shrub that produces various nutritional and bioactivecompounds. This research conducted to expand our knowledge about vitamin C andphysicochemical parameters in the maturation. The samples were obtained from the wildflora of La Unión, Huánuco and analyzed using standard techniques The vitamin C contentshowed a wide variation with significant differences in the fruit (p < 0.05), and the maturestate presented the higher content (181.86 ± 4.45 mg/100 g of fruit). The physicochemicalparameters presented a wide variation very marked in ripe fruits (p < 0.05). We also foundpositive correlations in the vitamin C content, pH, soluble solids, glucose but negative todensity of fruit and treatable acidity. In conclusion, B. lobbiana has a wide variation invitamin C and y in the physicochemical parameters of it fruits, mainly due to the influence ofgenetic factors, own of the maturation.